Syntheis of new chiral 5,6,7,8-tetrahydrotetrazolo[1,5-a]pyrazines from alpha-amino acid derivatives following ``click'' chemistry - Mohapatra, Debendra K.; Maity, Pradip K.; Ghorpade, Ravindra V.; Gurjar, Mukund K. (Heterocycles, 2009)
An efficient and practical synthesis of new chiral fused tetrazoles have been synthesized following [3+2] cycloaddition reaction starting from alpha-amino acid derivatives.
Keywords: Amino acid; Click chemistry; Hypertension; Nitrogen Rich System; Tetrazole

Synthesis of novel silica-polyimide nanocomposite films using aromatic-amino modified silica nanoparticles: mechanical, thermal and morphological investigations - Ghorpade, Ravindra V.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (Express Polymer Letters, 2015)
Silica nanoparticles were modified with aromatic amino groups and modified-silica/polyimide composite films were prepared using them. 3,3!, 4,4!-Benzophenone tetracarboxylic dianhydride (BTDA) and 4,4!-oxydianiline (ODA) were used as precursors for polyimide matrix. The structures of the modified nanoparticles and hybrid nanocomposites were identified using Fourier Transform Infrared (FTIR) spectrometry. The hybrid composite films were evaluated for mechanical, thermal and morphological characteristics. Morphological results describe a uniform dispersion of silica particles in the polymer matrix. The thermal stability and mechanical properties of polyimide composite were improved, and the decomposition temperature was increased when the amount of silica nanoparticles was increased.
Keywords: hybrid polyimide composites; mechanical properties; Nanocomposites; nanoparticle modification; Thermal properties

Synthesis and characterization of thermally stable polyimides with a pendent phenothiazine unit based on new diamine 10-(3,5-diaminobenzoyl)phenothiazine - Ghorpade, Ravindra V.; Thorave, Asmita K.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (High Performance Polymers, 2016)
A novel diamine 10-(3,5-diaminobenzoyl)phenothiazine (DBPT) with a side chain containing phenothiazine unit was synthesized. A new family of polyimides (PIs) containing phenothiazine unit in the side chains has been successfully synthesized by direct polycondensation of DBPT with pyromellitic dianhydride, 3,3',4,4'-benzophenone tertacarboxylic dianhydride, and 4,4'-oxydiphthalic anhydride (ODA) via a conventional two-step chemical imidization process. The yield of polymers was good enough, which were soluble in most organic solvents. The molecular orbital energy gaps, thermal stability, and crystallinity of PIs were investigated by molecular modeling, thermogravimetric analysis, and wide-angle X-ray scattering, respectively. Thermal properties of polymers were good enough to permit the use of these PIs in various applications; only 49% weight loss is detected at 900 degrees C in nitrogen atmosphere. X-Ray diffraction clearly reveals the amorphous nature of PIs. A quantum modeling study (density functional theory) has shown the influence of dianhydride structure on the energy difference of highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels.
Keywords: phenothiazine-containing diamine; Polyimide; thermally stable polymer

Synthesis of 2-phenoxy-2-phenylethyl acrylate and copolymerization with 2-phenylethyl acrylate: estimation of monomer reactivity ratios, thermal and optical properties - Ghorpade, Ravindra V.; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2016)
A new aromatic based monomer 2-phenoxy-2-phenylethyl acrylate (PPEA) was synthesized. Copolymers of PPEA with 2-phenylethyl acrylate (PEA) were prepared by free radical polymerization. The reactivity ratios were estimated using various graphical methods. Structural parameters of the copolymers were obtained by calculating the dyad monomer sequence fractions and the mean sequence length. Optical properties of polymers such as refractive indices and UV-Visible absorption were investigated. The glass transition temperature and thermal degradation behavior of the copolymers were studied. Combined with the RI, transparency and thermal properties, prepared copolymers hold great promise as materials for intraocular lens applications.
Keywords: 2-Phenoxy-2-phenylethyl acrylate; 2-phenylethyl acrylate; copolymerization; Optical properties; reactivity ratios; Thermal properties